Education for All: Reassessing the Historiography of Education in Colonial India - Ellis, Catriona (History compass, 2009)
This essay won the 2007 History Compass Graduate Essay Prize, Asia Section. Despite the extensive literature on the history of education in colonial India, historians have confined their arguments to very narrow themes linked to colonial epistemological dominance and education as a means of control, resistance and dialogue. These tend to mirror the debates of the colonial period, particularly regarding the Anglicist-Orientalist controversy. This article argues that such an approach is both gendered and hierarchical, and seeks to fundamentally redress the balance. It looks firstly at formal school education - colonial and indigenous - in both philosophical and technological terms. It then turns to education as experienced by the majority of Indian children outwith the classroom, either formally or within the domestic sphere. The article then looks at the neglected recipients of education, and seeks to re-establish children as agents within these adult-driven agendas. By considering educational discourse and practice, and the emerging historiography of Indian childhood and children, we can begin to establish a more rounded and inclusive picture of what education really meant.